Method for producing high crystallinity carbonaceous fibers with large crystal regions
Patent Information
- Application Number
- JP2024547162
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-16
- Filing Date
- 2022-04-08
- Publication Date
- 2025-02-21
AI Technical Summary
【0013】 本発明の有益な効果は、以下のとおりである。本発明は大サイズ酸化グラフェンの「構造テンプレート作用」と「誘導黒鉛化作用」を利用し、ポリマーの残炭率、黒鉛化度及び結晶化度を向上させる。一次元線形ポリマーと二次元グラファイトシート層のトポロジー幾何次元における不整合問題を解決することによって、二次元酸化グラフェンシートの幾何構造を利用し、一次元ポリマーを誘導して二次元類似グラフェンシート層を生成させる。大きなサイズの二次元酸化グラフェン(ポリマー比率がより高い)を少量添加するだけで、高結晶化度のグラフェン繊維材料を得ることを実現させ、これはグラフェン繊維の生成コストを低下させ、性能を向上させる方面に対して非常に有用である。同時にポリマーがグラフェンに触媒誘導される類似グラフェン層は繊維内部の黒鉛結晶のAB積層方式を調整することができ、グラフェン繊維の密度を増加し、黒鉛結晶領域の秩序ある配列を促進し、繊維内部の欠陥を低減することで、高強度、高弾性率、高導電性、高熱伝導性を一体とする高結晶化度グラフェン繊維材料を得ることができる。
Smart Images

Figure 2025505222000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of nanomaterials, and more particularly to a method for producing a highly crystalline carbonaceous fiber having large crystalline regions. [Background technology]
[0002] One-dimensional linear polymers are cheap and easy to obtain. In the industrial production of carbon fiber, they are mainly obtained by carbonizing and crystallizing one-dimensional linear polymer precursors at high temperatures. After the commercial polyacrylonitrile carbon fiber is carbonized at 1300 degrees, its mechanical strength is high, but the size of the graphite crystal domains inside is small and the arrangement is irregular, so its electrical and thermal conductivity is poor, with a thermal conductivity of 60 W / mK. After the high-temperature graphitization treatment at 2800 degrees, even if the size of the graphite crystal domains is slightly improved, it still cannot generate large-sized graphite crystal domains, and its thermal conductivity is only 300 W / mK at most. The essential cause is that due to the existence of an intrinsic topological geometric dimension mismatch caused by the one-dimensional polymer chains and the two-dimensional graphene sheet layers, the one-dimensional polymer molecular chains spontaneously carbonize and crystallize, and the crystals of the graphite crystal domains are disordered crystals, so the size of the three-dimensional carbonaceous crystal domains that are finally generated is small and has a low degree of orientation, and ultimately there are many electron / phonon scattering centers inside the fiber. Therefore, it is not possible to obtain a carbonaceous fiber that has high strength, high electrical conductivity, and high thermal conductivity.
[0003] Graphene was discovered in 2004 by Professor AK Geim's group at the University of Manchester in the UK, and won the Nobel Prize in Physics for proving that a perfect two-dimensional crystal structure can stably exist even at temperatures other than absolute zero. Specifically, graphene is a material in which carbon atoms are sp 2 It is a single-layer carbon atom crystal with a two-dimensional honeycomb structure interconnected by covalent bonds, with a mechanical strength of up to 120 GPa, a Young's modulus of up to 1.0 TPa, and a carrier mobility of up to 15,000 cm 2 / (V·s), and the thermal conductivity coefficient is up to 5300 W / mK. Therefore, using two-dimensional graphene sheet layers as the building blocks of macroscopic materials is a new route to develop new carbon macroscopic materials. The excellent physical and chemical properties of each element of graphene can be inherited in a controllable manner into the macroscopic assembly, thus improving the performance of carbon macroscopic materials in all aspects.
[0004] As a basic component element of the graphite crystal region, graphene can provide the optimal component element for macroscopic carbon materials with high strength, high electrical conductivity and high thermal conductivity. However, in the process of assembling nanomaterials into macroscopic materials, it is inevitable that many defects and cavities will be introduced, which will ultimately result in a difference between the performance of each macroscopic material and that of monolithic materials. It is a challenge to ensure the production of high-performance carbon fibers and to combine them with conventional commercial polymers to produce low-cost carbon fibers with high thermal conductivity. Conventional graphene / polymer composite materials mainly have several problems: First, because the graphene sheet diameter is relatively small and the raw materials for producing graphene or graphene oxide with small sheet diameters are relatively easy to obtain, the size of the graphene sheet diameter in most graphene / polymer composites is smaller than 10 micrometers, which cannot fully utilize the advantages of graphene as a two-dimensional topological geometric planar structure. Second, because graphene is difficult to arrange and orient in a disordered manner in the polymer and the graphene sheet diameter used is relatively small, graphene is difficult to form a liquid crystal phase in the dispersion and polymer solution. In order to form a liquid crystal phase, the content of graphene in the polymer needs to be significantly increased. However, when the proportion of graphene in the polymer is increased, the density of the entanglement of the chains in the polymer composite system will decrease due to the two-dimensional shielding effect of graphene. Therefore, the fluidity of the composite solution will be greatly weakened, which is unfavorable for the subsequent molding process. Taking the above two points into consideration, graphene cannot form a continuous network in the polymer system, and has a sea-island composite structure, and the interlayer limiting action of graphene is limited, so the molecular arrangement of the polymer body has a high degree of disorder, the crystallinity of the crystalline region is relatively low, and the polymer molecular chains can only be improved through processes such as subsequent stretching many times, which leads to the complexity of the process and the increase in cost. Thirdly, the oxidation degree and structural defect degree of graphene are not high. This is because most of the conventional graphene is added into the polymer system as a physical filler, and the chemical catalytic effect of oxygen-containing functional groups and structural defects as chemical groups of graphene itself is ignored. Therefore, the chemical properties of graphene itself are not fully exerted.
[0005] The present invention forms a liquid crystal composite solution by liquid-phase compounding a large-sized and highly oxidized single-layer graphene oxide sheet with a polymer precursor, and then performs post-carbonization treatment. Due to the two-dimensional topological geometric structure unique to graphene, the "two-dimensional structural template action" of the large-sized graphene flakes and the "induced graphitization action" of the oxygen-containing functional groups are used to solve the problem of inconsistency in the topological geometric dimensions between the one-dimensional linear polymer and the two-dimensional graphite sheet layer and the three-dimensional graphite crystal region, and thus a low-cost graphene carbonaceous fiber with high crystallinity is successfully prepared. Summary of the Invention
[0006] The object of the present invention is to improve the conventional industrialized manufacturing process of carbon fibers and provide a manufacturing process for obtaining high crystallinity carbonaceous fibers with large crystal domains and high thermal conductivity by utilizing inexpensive and readily available one-dimensional linear polymers.
[0007] Specifically, the present invention adds two-dimensional sheet-like seed crystals (graphene oxide) to one-dimensional linear polymer, wet spins the resulting composite yarn, and heats it to over 2000°C for 0.5-3 hours. Meanwhile, large-sized pieces of graphene oxide arrange and orient one-dimensional molecular chains of carbonizable polymers through a strong interlayer limiting effect, i.e., the "structural template effect" of graphene oxide brings about preferred orientation and crystallization, thereby producing composite yarns with high crystallinity. Meanwhile, the edge defects and surface oxygen-containing functional groups of graphene oxide serve as catalytic sites to induce graphene formation, thereby efficiently converting one-dimensional carbonizable polymers into two-dimensional graphene-like carbon layers.
[0008] In order to realize the structural template function and the graphene induction function, the following needs to be satisfied. (1) The size of the graphene oxide sheets is greater than 30 micrometers, and the carbon / oxygen ratio is greater than 0.5. (2) The one-dimensional linear polymer molecule is a carbonizable polymer, with a residual carbon ratio of 20% or more and an aromatization index of 0.8 or more. (3) The ratio of the carbon content of the two-dimensional sheet-like seed crystal to the carbon content of the polymer is 1:8.3 or more. (4) The solid content of the mixed solution is 3mg / g-30mg / g. The above four conditions are mutually complementary and essential. If the size of the graphene oxide sheet layer is smaller than 30 micrometers and the loading amount is low (less than 30%), it is difficult to form a continuous two-dimensional network sheet layer structure in the polymer matrix, and the crystal template function and space limiting function cannot be effectively realized. If the size is larger than 100 micrometers, the two-dimensional graphene oxide sheet that is too large is likely to form a folded structure, which prevents the formation of continuous seed crystal planes, and has a certain impact on the subsequent graphitization induction function. The carbon residue rate of the one-dimensional linear polymer molecule is preferably 20% or more and the aromatization index is greater than 0.8. If the carbon residue rate is too low, the one-dimensional linear polymer cannot form an effective intermediate phase to transform the topological structure, so it decomposes to generate a large amount of gas products, which makes it impossible to realize the graphitization induction function, and is prone to generate a porous structure inside the fiber. The higher the ratio of the carbon content of the two-dimensional sheet-like seed crystal to the polymer matrix, the higher the graphitization induction function and the carbon yield of the final heat-treated fiber, and the easier it is to generate the graphitization induction function. The concentration of the mixed solution is preferably controlled at 3mg / g-30mg / g. This concentration range is favorable for the actual spinning operation, and if the concentration is too low or too high, the difficulty of spinning will be greatly increased. The obtained fiber material has a high crystallinity, which can not only improve its mechanical strength, but also reduce the internal defects and disorder of the material and promote the internal transport of phonon electrons, thereby improving the electrical and thermal conductivity. High crystallinity graphene fiber is composed of multiple graphene sheets and similar graphene carbon layers, with a graphitization degree of more than 80% and a density of 1.8g / cm. 3The carbon content is greater than or equal to 80wt%. A number of graphite crystals in the fiber form electron and phonon paths, and the orientation degree of the graphite crystals it constitutes is greater than 80%, and the lateral size of the graphite crystals is greater than 100nm. The larger the size of the graphite crystals, the longer the electron and phonon free path, and the fiber material can have higher electrical and thermal conductivity. At the same time, the stacking manner of the graphite crystals inside the high crystallinity graphene fiber is mainly AB ordered stacking, which accounts for more than 50% of the total graphite crystal area inside the fiber, so the internal structure of the material is more uniform, there are fewer stress concentration points, and the material can achieve higher mechanical strength.
[0009] Specifically, the method includes the following processes: (1) Mix graphene oxide solution and polymer molecule solution uniformly. Here, the mass ratio of graphene oxide to polymer is 0.1-50:100, and the solid content of the mixed solution is 3mg / g-30mg / g. The ratio of graphene oxide to polymer is controlled to ensure that the mixed solution has typical liquid crystal properties and is spinnable. If the ratio of graphene oxide to polymer is too low, the final fiber will have low crystallinity and small graphite crystal regions. If the ratio is too high, the final fiber will have low density and high cost. (2) The liquid crystal composite spinning solution is spun by liquid crystal wet spinning technology, and the appropriate traction force is maintained during the spinning process, with the force value ranging from 0 to 100 MPa, and the fiber is not broken. Under the shear action of the extrusion flow field, the one-dimensional linear polymer molecules use the two-dimensional graphene oxide molecules as a structural template to carry out directed orientation crystallization, thereby realizing the "structural template action" of graphene oxide, and a composite yarn with high polymer crystallinity can be produced. Compared with polymer fibers without two-dimensional graphene oxide template, the polymer crystallinity inside the fiber is low, there is no directed arrangement, and the orientation degree is relatively low. The polymer crystallinity in the yarn is 40%-100%. (3) The dried high crystallinity composite yarn is subjected to high temperature heat treatment. Specifically, the temperature is raised to 2000°C or higher in a tube furnace and maintained for 0.5-3 hours. The graphene assembly material is crystallized to obtain the structure-function integrated graphene material. In the heat treatment process, the polymer molecules generate low molecular carbon sources during the pyrolysis process, and the two-dimensional graphene oxide can be converted into two-dimensional graphene sheet layers by removing surface functional groups and repairing defects. The two-dimensional graphene sheets utilize the characteristics of the sheet layer edges and sheet layer surfaces to induce and catalyze the molecules generated by polymer decomposition to perform directed assembly, thereby generating highly oriented similar graphene layers, and exhibiting the "induced graphitization effect" that realizes graphite crystal regions of high quality, large size, and high crystallinity. Compared with pure polymer fibers of oxygen-free graphene sheet layers, the graphite crystal regions generated inside them have low crystallinity and are extremely small in size (less than 8 nm).
[0010] During the high temperature treatment process, a traction force is applied, the force value of which ranges from 0 to 100 MPa, to ensure that the fibers do not break.
[0011] In the present application, the polymer is a polymer whose polymer molecules can be carbonized. The carbonizable polymer is composed of one or more of polyacrylonitrile (PAN), polyimide (PI), polyacrylamide, lignin, asphalt, phenolic resin, etc., having different molecular weights, mixed in any ratio.
[0012] The present invention also relates to the application of the high crystallinity graphene fiber material with the two-dimensional inductive effect in graphene materials with high strength, high elastic modulus, high electrical conductivity and high thermal conductivity, for example, the thermal conductive filler is used as a high thermal conductive composite material or a high electrical conductive composite material, and the high strength is utilized to prepare composite structural members.
[0013] The beneficial effects of the present invention are as follows: The present invention utilizes the "structural template effect" and "induced graphitization effect" of large-sized graphene oxide to improve the carbon residue rate, graphitization degree and crystallinity of the polymer. By solving the problem of inconsistency in the topological geometric dimension between the one-dimensional linear polymer and the two-dimensional graphite sheet layer, the geometric structure of the two-dimensional graphene oxide sheet is used to induce the one-dimensional polymer to generate a two-dimensional similar graphene sheet layer. By only adding a small amount of large-sized two-dimensional graphene oxide (with a higher polymer ratio), it is possible to obtain a graphene fiber material with high crystallinity, which is very useful in reducing the production cost of graphene fiber and improving its performance. At the same time, the similar graphene layer induced by the polymer to graphene can adjust the AB stacking mode of the graphite crystals inside the fiber, increase the density of the graphene fiber, promote the orderly arrangement of the graphite crystal region, and reduce the defects inside the fiber, thereby obtaining a graphene fiber material with high crystallinity that combines high strength, high elastic modulus, high electrical conductivity and high thermal conductivity. [Brief description of the drawings]
[0014] [Figure 1] Figure 1 shows the data on strength, elastic modulus, electrical conductivity, and thermal conductivity of the fibers obtained in Examples 1 and 2, in which the blue spheres indicate pure polymer fibers (polyacrylonitrile) and the red spheres indicate highly crystalline graphene fibers. [Diagram 2] FIG. 2 shows the internal graphite crystal region structure and selected electron diffraction patterns of the highly crystalline graphene fiber obtained in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention provides a method for producing a carbonaceous fiber with high crystallinity and large crystal regions, which is obtained by compounding a two-dimensional graphene oxide sheet with a one-dimensional linear polymer. Due to the unique two-dimensional topological geometric structure of the large-sized graphene oxide, the one-dimensional linear polymer can use it as a geometric template, and the "structural template action" can realize the directed assembly crystal of the polymer, so as to obtain a composite yarn with high crystallinity. Furthermore, due to the "induced graphitization action" of graphene during the heat treatment process, the polymer precursor can form a highly directed two-dimensional similar graphene layer, thus solving the problem of the inconsistency between one-dimensional and two-dimensional topological geometric dimensions, which is favorable for the formation of large-sized graphite crystals, and at the same time, the stacking manner of the graphene sheet layer can be adjusted to increase the proportion of AB-order stacking, so as to obtain a graphene fiber with high graphite crystallinity. Finally, a graphene material with high crystallinity can be obtained. The orientation degree of the graphite crystals is more than 80%, and the density is 1.8g / cm. 3 The lateral size (La) of each graphite crystal is in the range of 60-200 nm, the longitudinal size (Lc) of the graphite crystal is in the range of 10-30 nm, and the stacking manner of the internal graphite crystals is mainly AB ordered stacking, which accounts for more than 50% of the total graphite crystal area inside the fiber.
[0016] Example 1 In this example, carbon fibers were produced using one-dimensional linear polymer polyacrylonitrile (residual carbon ratio is 30% and aromatization index is 0.8), and the effect of the parameters of the two-dimensional sheet-like seed crystal for induction (see Table 1) on the performance was investigated as follows. (1) Polyacrylonitrile was uniformly dispersed in a pure DMF solution, and graphene oxide was added to form a spinning solution, so that the solid content of the system was 5%. (2) The liquid crystal composite spinning solution was extruded into a coagulation bath of pure ethyl acetate, and a high crystallinity composite fiber was obtained through a wet liquid crystal spinning process. An appropriate tensile force of 5N was maintained during the spinning process. (3) The raw yarn was placed in a tubular furnace, heated to 2000°C, and heat-treated for 3 hours at an atmospheric pressure of 10 MPa.
[0017] [Table 1]
[0018] The wide-angle X-ray diffraction test obtained the crystallinity of the composite yarn, the graphitization degree of the graphene fiber, the graphite crystal size, and the AB ordered stacking degree in the graphite crystal region, as shown in Table 2. The interlayer distance of the graphite crystal region is less than 0.35 nm.
[0019] The mechanical strength of the product was obtained by testing with Keysight T150U equipment, and the electrical conductivity was tested by the fiber four-wire method to obtain the electrical conductivity of the product graphene fiber, as shown in Table 2. The thermal conductivity test T-shaped method obtained the thermal conductivity of the product graphene fiber.
[0020] [Table 2]
[0021] The analysis of Sample 2 and Sample 1 in Example 1 reveals that the addition of 2D graphene oxide seed crystals can greatly improve the crystallinity of the raw fiber, and also generate a more perfect graphitization degree and graphite crystal domain size, thereby obtaining graphene fibers with high crystallinity and high thermal conductivity.
[0022] The analysis of Samples 2 and 3 in Example 1 shows that as the carbon / oxygen ratio of 2D graphene oxide gradually improves, the performance of the final graphene fiber is improved, which is due to the improvement of the carbon content ratio of the graphene oxide / polypropylene composite system, which improves the final carbon residue rate to a certain extent, and the graphitization induction effect of graphene oxide becomes more prominent, while graphene oxide still has liquid crystal properties, which can ensure the smooth progress of the liquid crystal spinning process.
[0023] The analysis of Sample 2 and Sample 4 in Example 1 shows that the more the carbon content and aromatization index of polyacrylonitrile increase, and the stronger the graphitization effect induced by the two-dimensional topological seed crystal, the more the performance of the final graphene fiber is gradually enhanced. If the carbon content of the polymer is too low, the graphene oxide cannot form an effective intermediate phase solid carbon product when it is graphitized, and the polymer will eventually escape as a carbonaceous gas-like small molecule, causing porosity inside the fiber, and ultimately fail to achieve graphene fiber with high crystallinity and high thermal conductivity.
[0024] The analysis of Samples 2 and 5 in Example 1 reveals that the performance of the final graphene fiber is gradually enhanced as the amount of 2D graphene oxide added increases and the graphitization effect induced by the 2D topology seed crystals is stronger. However, if the amount of the composite added is too small, the graphene oxide is difficult to form a liquid crystal phase in the polymer solution and cannot form a continuous 2D structure in the polymer matrix, so the crystallinity of the raw yarn and the graphitization of the graphene fiber cannot be improved, and the final graphene fiber with high crystallinity and high thermal conductivity cannot be achieved.
[0025] The analysis of Sample 2, Sample 6, Sample 7 and Sample 8 in Example 1 shows that as the size of 2D graphene oxide increases from small to large, the induced graphitization effect of 2D graphene seed crystals is gradually improved. If the sheet diameter size is too small, the advantage of graphene having a two-dimensional topological geometric plane structure cannot be fully exerted, but if the size of graphene oxide exceeds 150 μm, the large-sized single-layer graphene oxide sheet is likely to form a folded structure during the spinning process, which is unfavorable to inducing the formation of complete graphene crystals after heat treatment, which causes the crystallinity of the raw yarn and the graphitization degree of graphene to decrease to a certain extent, and the final mechanical properties and thermal conductivity properties of graphene fiber to decrease to a certain extent.
[0026] Example 2 In this example, different one-dimensional linear polymers (having different carbon residual ratios and aromatization indices) were employed to prepare carbon fibers as follows, as shown in Table 3. (1) The one-dimensional linear polymer was uniformly dispersed in pure DMSO solution, and graphene oxide was added to form a spinning solution, and the solid content of the system was 10%. The size of graphene oxide was 45±20 micrometers, and the carbon / oxygen ratio was 2.5. The ratio of the carbon content of the two-dimensional sheet-like seed crystal to the carbon content of the polymer was controlled to 0.76±0.02. The solid content of the mixed solution was 5 mg / g. (2) The liquid crystal composite spinning solution was extruded into a coagulation bath of pure ethyl acetate, and highly crystallinity composite fibers were obtained by a wet liquid crystal spinning process. (3) The raw yarn was placed in a tubular furnace, heated to 2000°C or higher, and heat-treated at an atmospheric pressure of 5 MPa.
[0027] [Table 3]
[0028] The wide-angle X-ray diffraction test obtained the crystallinity of the composite yarn, the graphitization degree of the graphene fiber, the graphite crystal size, and the AB ordered stacking degree in the graphite crystal region, as shown in Table 4. The interlayer distance of the graphite crystal region is less than 0.35 nm.
[0029] The mechanical strength of the product was obtained by testing with Keysight T150U equipment, and the electrical conductivity was tested by the fiber four-wire method to obtain the electrical conductivity of the product graphene fiber, as shown in Table 4. The thermal conductivity test T-type method obtained the thermal conductivity of the product graphene fiber.
[0030] [Table 4]
[0031] Analysis of the samples in Example 2 revealed that graphene oxide acts as a two-dimensional seed crystal to induce graphitization of polymers (polyimide, lignin, asphalt, phenolic resin) with a residual carbon ratio higher than 50%, ultimately resulting in graphene fibers with high crystallinity and high thermal conductivity.
Claims
1. A method for producing a high crystallinity carbonaceous fiber having large crystal regions, comprising the steps of: Two-dimensional sheet-like seed crystals are added to a one-dimensional linear polymer solution, mixed uniformly, and then wet-spun. The composite yarn obtained by spinning is heated to 2000° C. or higher and subjected to high-temperature treatment for 0.5 to 3 hours to obtain a highly crystalline carbonaceous fiber with large crystal regions. The two-dimensional sheet-like seed crystal is a graphene oxide sheet, the size of which is 30 micrometers or more, and the carbon / oxygen ratio is greater than 0.5; The one-dimensional linear polymer molecule is a carbonizable polymer, the carbon residual ratio is 20% or more, and the aromatization index is 0.8 or more; The ratio of the carbon content of the two-dimensional sheet-like seed crystal to the carbon content of the polymer is 1:8.3 or more; The method for producing a highly crystalline carbonaceous fiber having large crystal regions is characterized in that the solid content of the mixed solution is 3 mg / g to 30 mg / g.
2. 2. The method according to claim 1, wherein the polarity parameter of the coagulation bath used for wet spinning is 0.3-0.5, and the temperature of the coagulation bath is controlled at 40-70°C.
3. 2. The method according to claim 1, wherein the solvent of the mixed solution is one or more selected from the group consisting of water, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), N-methylpyrrolidone (NMP), dimethylsulfoxide (DMSO), ethanol, and glycerin, mixed in any ratio.
4. The one-dimensional linear polymer molecule is composed of one or more selected from polyacrylonitrile (PAN), polyimide (PI), polyacrylamide (PAM), lignin, asphalt, and phenolic resin, mixed in any ratio. The manufacturing method according to claim 1.
5. 2. The method according to claim 1, wherein traction is maintained during both the wet spinning process and the high temperature treatment process.
6. The application of the high crystallinity graphene fibers produced by the method according to claim 1 in graphene materials with high strength, high elastic modulus, high electrical conductivity and high thermal conductivity.
Citation Information
Patent Citations
Graphene fibers, yarns, composites, and methods for making the same
JP2020521063A